Pathogenesis and therapeutic applications of microglia receptors in Alzheimer’s disease - Fu, Jiao; Wang, RuoXuan; He, JiHui; Liu, XiaoJing; Wang, XinXin; Yao, JuMing; Liu, Ye; Ran, ChongZhao; Ye, QingSong; He, Yan (Frontiers in Immunology, 2025)
Microglia, the resident immune cells of the central nervous system, continuously monitor the brain’s microenvironment through their array of specific receptors. Once brain function is altered, microglia are recruited to specific sites to perform their immune functions, including phagocytosis of misfolded proteins, cellular debris, and apoptotic cells to maintain homeostasis. When toxic substances are overproduced, microglia are over-activated to produce large amounts of pro-inflammatory cytokines, which induce chronic inflammatory responses and lead to neurotoxicity. Additionally, microglia can also monitor and protect neuronal function through microglia-neuron crosstalk. Microglia receptors are important mediators for microglia to receive external stimuli, regulate the functional state of microglia, and transmit signals between cells. In this paper, we first review the role of microglia-expressed receptors in the pathogenesis and treatment of Alzheimer’s disease; moreover, we emphasize the complexity of targeting microglia for therapeutic interventions in neurodegenerative disorders to inform the discovery of new biomarkers and the development of innovative therapeutics